P PENGARUH PENDIDIKAN TERHADAP PENGETAHUAN BAHAYA MINUMAN KERAS RACIKAN PADA REMAJA - Muthmainnah Muthmainnah (LPPM Universitas Sari Mulia, 2021)
Background: Basic Health Research (Riskesdas) South Kalimantan Province the prevalence of population aged 10 years and over who consumed alcohol in the last 12 months in South Kalimantan Province 1.2% (range: 0.1-3.2%), districts/cities with a prevalence higher than provincial prevalence figures are Banjarmasin, Balangan, and Banjar. Oplosan drinks are pegged at low prices and consumers will get an extraordinary effect. However, the content of methanol in liquor accelerates the effects of drunkenness, can weaken the immune system, damage the liver, cause diarrhea and burning, inhibit concentration, slow reflexes, lose balance, damage the stomach, and even death. Objective: to determine the level of knowledge about the dangers of concoction of alcoholic beverages in youths of Gambut Kab. Banjar Methods: this study uses an experimental design with one group pre and posttest design, with a population of 430 people and the sample taken in this study was 78 respondents with details of 39 men and 42 women. In determining the sample, the researcher used a sampling technique, namely Stratified Random Sampling. In analyzing the data, the researcher used the Wilcoxon test. Results: the level of knowledge of respondents after being given education about the dangers of Conducted Drinks in adolescents increased from 66.7% to 75%. With the results of statistical tests using Wilcoxon showing a p value of 0.000, this value is statistically significant (p < 0.05) in this case it shows that there is an effect of providing education on the level of knowledge about the dangers of Conducted Drinks in adolescents. Conclusion: the conclusion that can be drawn from this research is that there is an effect of providing education on the level of knowledge about the dangers of Conducted Drinks in Adolescents.